Influence of Media Use Strip Story to Improve Writing Skills and Students’ Interest in Arabic Learning - Karim, Agus; Maryani, Novy; Noerhikmawati, Desti (Tadris Al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The research aims to determine how much strip story media use influences students' writing skills and interest in Arabic Learning in class X MA Daarul Uluum Majalengka. This thinking is that strip story media are pieces of paper often used in foreign language learning.Â Â Besides being cheap and easy to make, strip story techniques are simple and do not require special skills. This medium is effective in studying Arabic because it can provide skills for students and make them as fresh as learning, especially in Arabic writing skills. The study used normality, homogeneity, hypothesis (simple regression), and percentage tests. The result of this study was that students' ability to write without using Strip Story media in the control class was an average score of 74, a median of 87.50, a minimum of 52, and a maximum of 100. Students' ability to write skills using media strip stories in high experimental classes can be seen from the pre-test results with an average of 83, a median of 90.51,Â a minimum of 71, and a maximum ofÂ 100. Moreover, students' interest after using the media strip story gets a score of 72%, and this value is taken from those who strongly agree and agree.